(untitled) (Konturen, 2024)
It has become commonplace to consider Heimat a loaded concept. The origins of the malady of Heimat have been very convincingly laid out by Bilgin Ayata in her argument for a “deheimatization” of German cultural politics. Ayata deems this necessary as she considers every effort to salvage the concept through reclaiming or pluralization (Heimaten) as futile. While suggestions have been made out of social and cultural studies aiming to remedy its exclusionary and dangerous shortcomings, this article engages with literature’s potential for a “deheimatization” of German cultural spaces. In the study of three German novels by Kurdish authors, first access points are worked out: From rendering a German Heimat impossible through the destruction of the Kurdish homeland in Ronya Othmann’s The Summers (2020), and the disenchantment of a Kurdish Heimat as place of longing in Karosh Taha’s In the Queen’s Belly (2020), to the “deheimatizing” of the German Heimat in getting to know the Kurdish homeland thus far ignored in Imran Ayata’s My Name Is Revolution (2011). The present engagement with Kurdish-German literature provided some first access points towards a “deheimatization” of the German literary landscape and the canon, which could ultimately lead to new imaginaries of collectivity beyond the nation and thus beyond Heimat in its unsalvageable meaning. However, more theorizing is needed in order to render the concept of “deheimatizing” more fruitful for literary analyses.